Gravimetric geoid refinement using high resolution gravity and terrain data - Featherstone, Will; Alexander, K.; Sideris, M. (Institution of Surveyors, Australia, 1996)
In regions where additional, spatially dense gravity and terrain information are available to augment existing data, a gravimetric determination of the geoid can be improved by incorporating these new data. In this study, 4,016 additional gravity observations, measured on a near-regular 2km by 3km grid in Western Australia have been used to compute a gravimetric geoid model using fast Fourier transform (FFT) techniques. A digital terrain model is also used during the geoid computations, which is derived from gravity station elevations and spot heights in the area. Using 21 spirit-levelled Australian Height Datum (AHD) heights in conjunction with Global Positioning System (GPS) ellipsoidal heights as control data, the standard deviation of the new gravimetric geoid is ±0.0824m. This represents a 31% improvement over the existing AUSGEOID93 gravimetric geoid and a 48% improvement over the OSU91A global geopotential model. Of these improvements, approximately 10% is due to the additional gravity data and approximately 1% is due to the terrain effects; the remainder is due to the dense gridding of the data prior to the FFT computations.